INTERACTION OF LIQUID FLAT SCREENS WITH GAS FLOW RESTRICTED BY CHANNEL WALLS - S. T. Aksentiev; S. V. Glotov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper gives description of physical pattern of liquid screen interaction that are injected from the internal walls of a rectangular channel with gas flow. Criterion dependences for determination of intersection coordinates of external boundaries with longitudinal channel axis and factor of liquid screen head resistance.